Hydrogen peroxide formation in the interaction of oxygen with boron-containing Pd catalysts prereduced by hydrazine in aqueous acidic medium containing bromide anions - Choudhary, Vasant R.; Samanta, C. (Catalysis Letters, 2005)
Interaction of molecular oxygen with Pd/BPO4 or ZrO2 (or Al2O3, CeO2, TiO2) - B2O3 catalysts, prereduced by hydrazine hydrate, in an aqueous acidic (H2SO4 or H3PO4) reaction medium containing bromide ions leads to the formation of H2O2. However, in the absence of boron in the catalyst and also in the absence of acid and/or bromide ions in the reaction medium, almost no H2O2 is formed.
Keywords: boron-containing Pd catalysts; Hydrogen peroxide; oxygen-catalyst interactions